EXPLOITATION RESEARCHES ON FORESTRY MILLING MACHINES FOR SOIL PREPARATION AT THE TERRITORY OF SHUMEN NORTH-EAST STATE FORESTRY - Marinov, Konstantin; Kostov, Konstantin (Innovation in Woodworking Industry and Engineering design, 2022)
Forestry milling machines for soil preparation of afforestation are featured by higher technological and ecological properties, but also with higher energy costs, compared to the traditional machines used in our country. This paper presents the results of the conducted experimental studies to establish the main operational properties of forestry milling machines for complete soil preparation for afforestation in the lower forest vegetation zone in Bulgaria. The study were carried out with FAE SSH/HP 250 forest tiller in experimental sites located in open forest areas, forest fellings and field protection forest belts on the territory of the Shumen Forest North-East State Enterprise. The fuel consumption and productivity for complete soil preparation of open forest areas and clearings with stumps of hardwood species, with an average stumps diameter from 10 cm to 38 cm and stumps density from 220 pcs/ha to 1310 pcs/ha, at tilling depth up to 40 cm, at different rotation speed of the tiller were determined. Based on the obtained results, regression models were developed to determine the main operational indicators of the forest cutters and the optimal operating modes of the machines under certain working conditions were established.